Low-Threshold 795 nm Oxide-Confined Distributed Feedback Lasers With Surface Gratings - Pingping Qiu; Hengjie Zhou; Tongxin Wang; Qiuhua Wang; Qiang Kan (IEEE Photonics Journal, 2023)
795 nm oxide-confined distributed feedback (DFB) lasers have been developed. The oxide-confined structure is used to realize lateral optical and current confinement, and the first-order surface gratings offer the frequency selectivity for single-longitudinal mode operation. The fabricated 200-μm-long devices exhibited a low-threshold current of ∼4.8 mA, a 3-dB modulation bandwidth of ∼5.8 GHz and maintained stable single mode operation around 795 nm with side mode suppression ratio (SMSR) as high as ∼40 dB. The simple and compact laser structure greatly reduces the difficulty of device design and fabrication compared with traditional DFB lasers. The characteristics of the laser, including low-threshold current, single mode stability and potentially narrow spectral linewidth, make it a suitable candidate for applications in absorption spectroscopy of the rubidium D1 line, chip-scale atomic clocks, magnetometers, and gyroscopes.